Acurácia de diferentes indicadores para avaliar o estado nutricional de adultos - Pereira, Guilherme Adroaldo (2016)
The present study had as objective to analyze the accuracy of different indicators of the nutritional status of adults of both sexes, having as reference method the hydrostatic weighing (HW). A total of 280 subjects (210 men and 70 women), aged between 17 and 48 years old, were investigated. The results of body fat percentage (%BF) obtained through the University of Navarra-Body Adiposity Estimator (CUN- BAE), body adiposity index (BAI), skinfold estimation equations (E-DC) and bioelectrical impedance (BIA). We also analyzed the results of the body mass index (BMI), new body mass index (BMI2.5), body fat mass index BFMI and the body mass index adjusted by the fat mass (BMIfat), all of them using HW as the reference method. The results indicated that no significant differences were observed between the %BF measures of the E-DC and BIA indicators and the HW for the male group; however, for the female group, despite the analyzes indicating agreement, the %BF values presented statistically different from those obtained with the reference method. The BAI presented an acceptable estimation error when evaluating the female group and the CUN-BAE presented a tendency to overestimate the values of %BF, in both sexes. On the other hand, the BFMI presented the highest agreement value, but classified as discrete (k=0.21). The other indexes presented small agreement with the results of the reference method (k <0.20). It is possible to conclude that, in a general way, the E-DC and BIA indicators were the ones that presented the best results, with the E-DC being more efficient to evaluate the male subjects. In addition, none of the indexes investigated showed good accuracy in assessing the nutritional status of adults, although they showed results of correlation with the reference method, did not reach the minimum criterion of agreement.